Driving Style Modelling for Eco-driving Applications. Issue 1 (July 2017) - Javanmardi, S.; Bideaux, E.; Trégouët, J.F.; Trigui, R.; Tattegrain, H.; Bourles, E. Nicouleau
Abstract: Driver modeling is an important subject in transportation systems and intelligent vehicles. These models can replace human driver to quantify and enhance the technological solutions by means of simulation. In this paper a driving style model for representing three different styles is proposed. Simulation results on two road types are presented and the fuel consumption estimation obtained with this model is discussed. The model could then be used jointly with a trajectory optimization algorithm for designing an eco-driving advance driving assistance system (ADAS) for reducing fuel consumption which is adaptive to the driving style.